Water Proton NMR for In Situ Detection of Insulin Aggregates. Issue 12 (7th September 2015) - Taraban, Marc B.; Truong, Huy C.; Feng, Yue; Jouravleva, Elena V.; Anisimov, Mikhail A.; Yu, Yihua Bruce
Abstract : The need for quality control during the manufacturing and distribution of biopharmaceuticals is becoming increasingly necessary. At present, detecting drug degradation through the monitoring of active factor aggregation is accomplished through "invasive" techniques, such as size‐exclusion chromatography (SEC), analytical ultracentrifugation (AUC), and so on. Unfortunately, these analytical methods require sampling the drug by opening the drug container that renders the remaining drug unusable regardless of the outcome of the test. Visual inspection, the current non‐invasive quality control method is qualitative and can only detect visible particulates. Thus, it will miss sub‐visible protein aggregates. In this paper, human insulin preparations were used to demonstrate that the transverse relaxation rate of water protons R 2 ( 1 H2 O) can serve as a sensitive and reliable indicator to detect and quantify both visible and sub‐visible protein aggregates. R 2 ( 1 H2 O) is measured using a wide‐bore low‐field bench‐top NMR instrument with permanent magnets. Such analysis could be carried out without opening the drug container, thus saving a drug for further use. The results suggest a novel, economical, non‐destructive in situ analytical technique that allows for on‐the‐site quantification of protein aggregation in biopharmaceutical products. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4132–4141, 2015